Faunistic review of Tetratomidae and Melandryidae (Coleoptera: Tenebrionoidea) in Lithuania with an annotated checklist of the species - Tamutis, Vytautas; Ferenca, Romas; Pollock, Darren A. (Zootaxa, 2019)
This paper presents the first faunistic review of species composition and distribution of Tetratomidae and Melandryidae (Coleoptera: Tenebrionoidea) in Lithuania. An annotated checklist of the species is given. The peculiarities of some morphological structures of Dircaea australis, Phloiotrya subtilis, Orchesia fusiformis, O. micans and Zilora cf. obscura are briefly reviewed and illustrated. Information on five species of Tetratomidae and twenty-two species of Melandryidae is given, including faunistic data, prior records, general distribution, and notes on frequency, ecology and morphological peculiarities of some species. Eustrophus dermestoides (Tetratomidae), Phloiotrya rufipes, Hypulus bifasciatus and Phryganophilus ruficollis (Melandryidae) known from previous literature records are excluded from the Lithuanian fauna due to suspect data on their occurrence in the country. Phloiotrya subtilis and Orchesia fusiformis are recorded from Lithuania for the first time. The presence of Tetratoma fungorum and Abdera flexuosa in the Lithuanian fauna was confirmed by actual faunistic data, which were previously absent. Four species of Tetratomidae and 19 species of Melandryidae are confidently included in the Lithuanian fauna, corresponding to 50% of the total European fauna of both families excluding regional endemics.